2003
DOI: 10.1002/ana.10548
|View full text |Cite
|
Sign up to set email alerts
|

Toward therapy for DYT1 dystonia: Allele‐specific silencing of mutant TorsinA

Abstract: A three-nucleotide (GAG) deletion in the TOR1A gene is the most common cause of inherited dystonia, DYT1. Because the mutant protein, TorsinA (TA), is thought to act in a dominant manner to cause disease, inhibiting expression from the mutant gene represents a potentially powerful therapeutic strategy. In an effort to develop therapy for this disease, we tested whether small interfering RNA (siRNA) could selectively silence expression of mutant TA. Exploiting the three-base pair difference between wild-type an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 28 publications
2
73
0
Order By: Relevance
“…The potency and selectivity of this approach has recently been documented for several dominant disease genes (27,28), including SOD1. Our findings confirm and extend the recent report of Ding et al (29), which described RNAi-mediated, allele-specific silencing of the SOD1 G85R and SOD1 G93A alleles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potency and selectivity of this approach has recently been documented for several dominant disease genes (27,28), including SOD1. Our findings confirm and extend the recent report of Ding et al (29), which described RNAi-mediated, allele-specific silencing of the SOD1 G85R and SOD1 G93A alleles.…”
Section: Discussionmentioning
confidence: 99%
“…In recent months, several studies have reported RNAi-mediated inactivation of dominant disease alleles differing from their wild-type counterparts by a single nucleotide (27,28), and one report demonstrated specific inhibition of mutant SOD1 alleles (29). The present study confirms and extends these observations and identifies previously uncharacterized siRNA sequences for selective silencing of FALS-linked mutant SOD1.…”
mentioning
confidence: 99%
“…The various torsinA expression plasmids used for this study have been described previously (Gonzalez-Alegre et al, 2003). To generate the U6shRNA constructs, we used a PCR-based approach described previously (Harper et al, 2005), with primers designed to generate the different hairpins shown in Figure 1: five hairpins targeting torsinA(⌬E) (U6shTAmut1-5) and three control hairpins, one targeting torsinA(wt) (U6shTAwt), one targeting a sequence common for both for human and murine torsinA (U6shTAcom), and a mismatched sequence not targeting either allele as shown previously (U6shTAmis) (Gonzalez-Alegre et al, 2003). The PCR product was ligated into the pCR2.1 vector using the TOPO-TA Cloning kit (Invitrogen, San Diego, CA) and the product verified by sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…The PCR product was then inserted into the multiple cloning site of pcDNA3.1 (Invitrogen). Additional plasmids included GFP-Q19 (GFP fused to a stretch of 19 glutamines), torsinA(wt)-GFP (a kind gift from Dr. P. Hanson, Washington University, St. Louis, MO) (Naismith et al, 2004), and HA-torsinA(⌬E) (Gonzalez-Alegre et al, 2003). Feline immunodeficiency virus (FIV) pseudotyped with VSV-G (vesicular stomatitis virus G) were generated by the Gene Transfer Vector Core of the University of Iowa (www.uiowa.edu/ϳgene/) as described previously (Brooks et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation